Deteksi Dini Pertumbuhan dan Perkembangan Anak - Dini Nurbaeti Zen; Daniel Akbar Wibowo; Durotul Aeni Zakiyah (Yayasan Inspirasi El Burhani, 2022)
Introduction: Growth and development are two separate events and cannot be separated. A comprehensive and quality examination of children's growth and development carried out through stimulation activities, early detection and intervention of deviations in growth and development of toddlers should be carried out during the golden period, namely the first 5 (five) years of a child's life. Monitoring and stimulation of child growth and development is very necessary for optimizing children's growth and development and recognizing problems early. Objective: The purpose of this service is to increase promotive and preventive efforts in increasing the growth and development of toddlers by increasing the knowledge and skills of mothers of toddlers in stimulating the growth and development of their children and increasing the ability of mothers in early detection of disorders of growth and development of toddlers in the Public Health Center of Panjalu. Method: The methods used in this community service are lectures and discussions. Result: The service activity was carried out for 2 days, namely on 12-13 October 2021 which was attended by 27 mothers. The results of community service for mothers who have received health education are enthusiastic to monitor the growth and development of their children, mothers of toddlers know and understand how to detect growth and development provided by the community service team. Conclusion: In addition, the detection of children in the working area of Public Health Center of Panjalu showed that most of them (88.9%) growth and development were in accordance with the stages of age.